Acute flaccid Paralysis as first presentation of Primary Sjogren’s Syndrome: A case report from Nepal - Thapaliya, Abhishek; Shah, Bhupendra; Chhetri, Roshan; Uprety, Auraj; Dhakal, Deepak; Sharma, Sanjib Kr (Journal of Advances in Internal Medicine, 2021)
Sjögren’s syndrome is an autoimmune disease with glandular and extra-glandular involvement. The common neurological manifestation of Sjögren’s syndrome are peripheral neuropathy, anterior horn cell disease, transverse myelitis and aseptic meningitis. However, Sjögren’s syndrome presenting with acute flaccid paralysis is rare phenomenon. We report a case of a 35-year-old woman who presented with acute flaccid paralysis with respiratory failure who was later diagnosed as Primary Sjogren’s syndrome.